About Time : A History Of Civilization In Twelve Clock - Rooney, David (UK Penguin Books, 2022)
The measurement of time has always been essential to human civilisation, from early Roman sundials to the advent of GPS. But while we have one eye on the time every day, are we aware of the power clocks have given governments, military leaders and business owners, and how they have shaped our lives and our world? In this spectacularly far-reaching book, David Rooney narrates a history of timekeeping and civilisation in twelve concise chapters. Over their course, we meet the most epochal inventions in horological history, from medieval water clocks to Renaissance hourglasses, and from stock-exchange timestamps to satellites in Earth's orbit. We discover how clocks have helped people navigate the globe and build empires, but also, on occasion, taken us to the brink of destruction. This is the story of time, and the story of time is the story of us
Include Illustration And Index
Keywords: Civilization -- Horology -- Time--Social aspects -- Clocks and watches -- Time